Design of ballasted railway track foundations using numerical modelling: Part II: Applications - Sayeed, M.; Shahin, Mohamed (NRC Research Press, 2018)
This paper is the second of two companion papers in relation to a new design method for ballasted railway track foundations. Development of the new design method has been explained in the first paper (i.e., Part I: Development), and the procedures for using the method and its practical application on some field case studies are presented in this paper. A special feature of the proposed design method is that it considers the true impact of train dynamic moving loads and number of repeated applications of the traffic tonnage. The proposed method is applied to four case studies of actual tracks and the results are compared with field measurements and found to be in good agreement. It should be noted that, although the proposed design method is able to overcome most shortcomings of the existing methods and found to provide excellent outcomes, further verification with more field case studies is highly desirable.